2017
DOI: 10.1111/crj.12647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the genetic variants of GLCCI1 on clinical features of asthmatic patients

Abstract: A worsening of pulmonary function caused by GLCCI1 variants could be prevented due to recently used medications based on new action mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…(2, 5) Although these variants have fairly large effect sizes, in the case of GLCCI1 , GWAS indicated up to 6% of variation in response to ICS treatment,(4) but attempts at clinical validation have produced mixed results. (69) These findings suggests that additional genes may be important for determining ICS response in asthma. (10)…”
Section: Introductionmentioning
confidence: 94%
“…(2, 5) Although these variants have fairly large effect sizes, in the case of GLCCI1 , GWAS indicated up to 6% of variation in response to ICS treatment,(4) but attempts at clinical validation have produced mixed results. (69) These findings suggests that additional genes may be important for determining ICS response in asthma. (10)…”
Section: Introductionmentioning
confidence: 94%
“…Chiba et al reported that GLCCI1 was shown to be positively localized on bronchial epithelial cells and exhibit lower expression in asthma but higher expression with fluticasone stimulation ( 9 ). Therefore, Beas2B and A549 cells were used in this study to investigate the effect of GLCCI1 in epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our own previous data showed that GLCCI1 variations are associated with asthma susceptibility and the ICS response in the adult Chinese Han population and that GLCCI1 expression might be affected by variations in GLCCI1 during the ICS response period ( 8 ). Additionally, GLCCI1 was positively localized on bronchial epithelial cells, and its variants could influence GC sensitivity ( 9 ). Therefore, GLCCI1 expressed on epithelial cells plays a crucial and important role in mediating the GC response in asthma, which might be beneficial for bio-identification, but the potential mechanism is not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…High-dose inhaled corticosteroid treatment increased the pulmonary function of patients homozygous for IL13 AA of rs20541 but not of patients homozygous for STAT4 TT of rs925847 [ 22 ]. Another analysis revealed an association between the homozygous GLCCI1 rs37972 and rs37973 and the asthmatic treatment steps used with the Japanese population, showing an OR of 2.78 and 2.28, respectively, but not with pulmonary function [ 23 ]. We concluded that the recent wide use of anti-IgE and tiotropium produced a clinically meaningful reduction in the exacerbation rate and a sequential improvement in pulmonary function.…”
Section: Discussionmentioning
confidence: 99%